Seduction on a snowy night eaudiobook - Putney, Mary Jo (Recorded Books Inc., 2019)
This winter, steal away with the reigning queens of Regency Romance . . . to a surprise snowstorm, the comfort of a blazing fire, and the heat of a lover's kisses . . . A CHRISTMAS ABDUCTION by Madeline Hunter Caroline Dunham has a bone to pick with notorious rake Baron Thornhill-and a creative plan to insure his undivided attention. Yet once in close quarters, she finds herself beholden to their smoldering connection . . . A PERFECT MATCH by Sabrina Jeffries Whisked away from a wintry ball by the officer she knew only through letters, Cassandra Isles struggles with her feelings for the commanding Colonel Lord Heywood. For he, secretly a fortune-hunter, must marry for money to save his estate-and Cass, secretly an heiress, will accept nothing less than love . . . ONE WICKED WINTER NIGHT by Mary Jo Putney Dressed as a veiled princess, Lady Diana Lawrence is shocked to discover that the mysterious corsair who tempts her away from the costume ball is the duke she once loved and lost. Now snowed in with Castleton at a remote lodge, will she surrender to the passion still burning hotly between them?